RELASI AGAMA DAN NEGARA - Gunawan, Edi (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2017)
This paper examines religious and state relations of Islamic thought perspective. This study aims to describe how the relationship between religion and state in the view of Islam. The method used in obtaining data is descriptive method through literature study. The results of the study show that among Muslim figures or thinkers such as Nurcholish Madjid and Abdur Rahman Wahid agree that there is a constructive relationship between state and religion which by revivalists separates it. Some of the indicators are: (1) Islam gives the principles of the formation of a state with the concept of khalÄ«fah ,dawlah, or hukÅ«mah, (2) Islam emphasizes the democratic values of truth and justice, and (3) Islam upholds Human Rights by stating that the basic rights that human beings bring ever since they are born are the right of religious freedom. Therefore, Islam essentially emphasizes the importance of human rights to be upheld in a state, because human rights are rights that should not be disturbed and deprived from the person who has the right.